Entry-to-Practice Requirements and Regulation in Canadian Social Work - Rice, Ian (Canadian Social Work Review / Revue canadienne de service social, 2025)
This paper examines entry-to-practice requirements used by social work regulatory organizations to protect the public. It reviews registration standards in Canada’s eleven regulated jurisdictions, drawing on jurisdictional legislation, regional regulatory documents, and interviews with social work professionals. Findings show that competency-based assessment is expanding regulatory influence on the profession. This paper is valuable to social work students and new graduates in Canada to assist in understanding entry to the profession. Current and future trends in entry-to-practice requirements both reflect and contribute to challenges for social work.